Developing a standardized approach to the assessment of pain in children and youth presenting to pediatric rheumatology providers: a Delphi survey and consensus conference process followed by feasibility testing - Stinson Jennifer N; Connelly Mark; Jibb Lindsay A; Schanberg Laura E; Walco Gary; Spiegel Lynn R; Tse Shirley ML; Chalom Elizabeth C; Chira Peter; Rapoff Michael (BMC, 2012)
Abstract Background Pain in children with rheumatic conditions such as arthritis is common. However, there is currently no standardized method for the assessment of this pain in children presenting to pediatric rheumatologists. A more consistent and comprehensive approach is needed to effectively assess, treat and monitor pain outcomes in the pediatric rheumatology population. The objectives of this study were to: (a) develop consensus regarding a standardized pain assessment tool for use in pediatric rheumatology practice and (b) test the feasibility of three mediums (paper, laptop, and handheld-based applications) for administration. Methods In Phase 1, a 2-stage Delphi technique (pediatric rheumatologists and allied professionals) and consensus meeting (pediatric pain and rheumatology experts) were used to develop the self- and proxy-report pain measures. In Phase 2, 24 children aged 4-7 years (and their parents), and 77 youth, aged 8-18 years, with pain, were recruited during routine rheumatology clinic appointments and completed the pain measure using each medium (order randomly assigned). The participant's rheumatologist received a summary report prior to clinical assessment. Satisfaction surveys were completed by all participants. Descriptive statistics were used to describe the participant characteristics using means and standard deviations (for continuous variables) and frequencies and proportions (for categorical variables) Results Completing the measure using the handheld device took significantly longer for youth (M = 5.90 minutes) and parents (M = 7.00 minutes) compared to paper (M = 3.08 and 2.28 minutes respectively p = 0.001) and computer (M = 3.40 and 4.00 minutes respectively; p < 0.001). There was no difference in the number of missed responses between mediums for children or parents. For youth, the number of missed responses varied across mediums (p = 0.047) with the greatest number of missed responses occurring with the handheld device. Most children preferred the computer (65%, p = 0.008) and youth reported no preference between mediums (p = 0.307). Most physicians (60%) would recommend the computer summary over the paper questionnaire to a colleague. Conclusions It is clinically feasible to implement a newly developed consensus-driven pain measure in pediatric rheumatology clinics using electronic or paper administration. Computer-based administration was most efficient for most users, but the medium employed in practice may depend on child age and economic and administrative factors.